PENGUJIAN BLACKBOX APLIKASI FORECASTING FTTH BERBASIS WEBSITE (STUDI KASUS PADA PT YOFC INTERNATIONAL INDONESIA) - Moch Viqqy Fajar Aditya; Agus Satrio Utomo; Yusril Sadhanayoga; Aries Saifudin (CV. Multi Kreasi Media, 2024)
Web-based, desktop or mobile applications before being used to the general public or certain companies must pass testing on the software. There are two methods in testing that we usually know, namely Black Box Testing and White Box Testing. For this time the testing method we chose was Black Box Testing with the Equivalence Partitions Technique which aims to test whether there are errors in: system functions, interfaces, data structures or data access, performance, initialization. The object carried out in this test is the Website-Based FTTH Material Forecasting application. The methods and techniques chosen in this test are techniques that are easy to do for novice testers. There are 4 forms tested, namely user and admin login forms, product forms, category forms, project forms. Each form will be tested by entering input data that is commonly found in existing tests. The results showed that software testing using the Black Box Testing method with the Equivalence Partitions Technique in the application there are still forms whose results or outputs do not match what is expected in the design of the application because an error occurs. The results of the calculation of system validity obtained a value of 100%.